Real-Time Aeroelastic Hybrid Simulation of a Base-Pivoting Building Model in a Wind Tunnel - Moni, Moniruzzaman; Hwang, Youchan; Kwon, Oh-Sung; Kim, Ho-Kyung; Jeong, Un Yong (Frontiers in Built Environment, 2020)
The wind tunnel test is one of the most reliable methods for evaluating the dynamic response of high-rise buildings in regards to wind-structure interaction. In conventional aeroelastic wind tunnel tests the calibration of stiffnesses, masses and the damping properties of a scaled specimen is required. This takes extensive time and effort, especially when the tests need to be repeated with various geometric designs during design iterations. This study introduces a new testing method that combines a numerical simulation and the conventional aeroelastic wind tunnel test through the real-time hybrid simulation method. The stiffness, damping and partial mass of a scaled building model are represented numerically, while the rest of the mass, the wind-induced pressure around the model and the wind-structure interaction are represented physically in a wind tunnel. The building model in the wind tunnel rests on a base-pivoting system, which is controlled with a linear motor. The base moment induced by wind pressure and the inertial force from the mass of the physical specimen are measured; those measurements are then fed back into a numerical integration scheme. A delay-compensation scheme is implemented to minimize the effects of actuator delay on the dynamic response of the system. Several tests are carried out to validate and calibrate the developed test apparatus and control scheme including 1) tests for the identification of actuator delay, 2) free vibration tests for characterization of the dynamic properties of the hardware and the control system and 3) wind tunnel tests for system validation through aeroelastic real-time hybrid simulation. This paper presents the overall design of the experimental apparatus, the adopted delay compensation and numerical integration schemes, and a summary of the test results. Test results confirmed that the developed experimental technique can replace the conventional aeroelastic wind tunnel tests of a building model, thus improving the efficiency of the aeroelastic wind tunnel testing.